The Role of Religious Law in Combating and Preventing Crime in Developing Nations - Suprijati Sarib; Sabil Mokodenseho (Westscience Press, 2023)
This research aims to explore the role of religious law in preventing and tackling crime in developing countries, focusing on the challenges and opportunities faced. The research method used is descriptive-qualitative, with data collection through interviews, observations, and document studies. The results showed that religious law has great potential in preventing and dealing with crime in developing countries, especially in terms of prevention through the formation of individual character and morals. However, the challenges faced are the conflict between religious law and secular law and the weak implementation of religious law. The opportunities exist through collaboration between religious law and secular law and strengthening the performance of religious law that can be done through education and training for law enforcers. This research is expected to contribute to developing legal policy and practice in developing countries, especially regarding crime handling.